Analysis of HOTS Question Items for Bahasa Indonesia Final Assessment for VIIth Grade Students at MTs Negeri 6 Boyolali - Margareta, Tricia; Hidayatullah, Rahmat Wahyu; Andrea Qaulan Tsaqila Hasfin; Lisa Wahyuningsih (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This journal article aims to analyze the High Order Thinking Skills (HOTS) questions in the Odd Semester Final Assessment (PAS) for class VII in the Indonesian language subject at MTs Negeri 6 Boyolali. The research method used is descriptive qualitative, by collecting and analyzing data from questions applied in PAS for Indonesian Language subjects. The research results show that most of the questions have a level of difficulty that is appropriate to students' abilities. However, there are several questions that still need to be improved in order to trigger students' higher thinking abilities. The conclusion of this research is the importance of compiling and selecting questions that are appropriate to the learning objectives in order to optimize the development of students' high-level thinking abilities.